External Factors on Composite Stock Price Index with Inflation as a Moderation - Nur Afni Yunita; Muhammad Yusra; Rany Gesta Putri Rais; Sri Mulyati (Department of Accounting, Faculty of Economics & Business, 2025)
This study aims to determine the effect of crude oil prices, gold prices and the DJIA Index on the movement of the IHSG with inflation as a moderation. The study used 48 observation data with the MRA technique. The results of the study showed that crude oil prices had a positive effect, gold prices had a negative effect and the DJIA Index had no effect on the movement of the IHSG. Inflation was also able to moderate the effect of crude oil prices, gold prices and the DJIA Index on the movement of the IHSG